ANALISIS LAPORAN KEUANGAN MENGGUNAKAN RASIO KEUANGAN DAN COMMON SIZE UNTUK MENILAI KINERJA KEUANGAN PT BANK AMAR INDONESIA - Hotma Tua Sihombing, Elsa Monica; Nurlinda (Politeknik Negeri Medan, 2024)
This final report is entitled Financial Statement Analysis Using Financial Ratios and Common Size to Assess the Financial Performance of PT Bank Amar Indonesia (2019-2022 Period). This final report aims to determine the financial performance of PT Bank Amar Indonesia. The source used is secondary data with documentation data collection. Documentation in the form of financial statements. Data processing uses formulas and describes the results. The results show that the Financial Ratio and Common Size formulas can assess the financial performance of PT Bank Amar Indonesia (2019-2022 period). Financial performance of PT Bank Amar Indonesia (Period 2019- 2022) is declared fluctuating.